2022
DOI: 10.1097/cm9.0000000000002096
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and its emerging roles in acute pancreatitis

Abstract: Acute pancreatitis (AP) is a common and potentially life-threatening pancreatic inflammatory disease. Although it is usually selflimiting, up to 20% of patients will develop into severe AP. It may lead to systemic inflammatory response syndrome and multiple organ dysfunction, affecting the lungs, kidneys, liver, heart, etc. Surviving patients usually have sequelae of varying degrees, such as chronic hyperglycemia after AP (CHAP), pancreatic exocrine insufficiency, and chronic pancreatitis. Lacking specific tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…It has been suggested that ferroptosis exacerbates pancreatic injury in AP. 50 Recent research indicates that elevated levels of extracellular trypsin increase susceptibility to ferroptosis rather than apoptosis and necroptosis in pancreatic acinar cells. 51 The protective effects against AP can be observed by the treatment of β-hydroxybutyrate, 52 Wedelolactone, 12 and Ginsenoside Rg3 53 through the inhibition of ferroptosis of pancreatic acinar cells.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It has been suggested that ferroptosis exacerbates pancreatic injury in AP. 50 Recent research indicates that elevated levels of extracellular trypsin increase susceptibility to ferroptosis rather than apoptosis and necroptosis in pancreatic acinar cells. 51 The protective effects against AP can be observed by the treatment of β-hydroxybutyrate, 52 Wedelolactone, 12 and Ginsenoside Rg3 53 through the inhibition of ferroptosis of pancreatic acinar cells.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[100] Recent Advances of Ferroptosis in AL In recent years, studies related to ferroptosis have emerged, and many studies have shown that ferroptosis is closely related to the occurrence and development of tumors. [26,38,[101][102][103][104] Here, we focus on AL and report that ferroptosis affects the occurrence and development of AL through various pathways, including various signaling pathways, natural extracts, drugs, compounds, ferroptosisrelated molecules, and so on [Figure 3 and Table 1].…”
Section: Gpx4-independent Pathwaymentioning
confidence: 99%
“…15 As a form of regulation of programmed cell death, ferroptosis is involved in the damage process of acinar cells in SAP, which can disrupt the balance between ROS production induced by iron accumulation and the antioxidant system within lipid peroxidation. 16,17 As a lipid repair enzyme, GPX4 is a key factor of ferroptosis, and the dysfunction or abnormal level of FTH1 will cause an increase in intracellular iron amount, allowing us to promote the occurrence of ferroptosis. 16,18 However, research of SAP treatment is still at a preliminary stage of exploration, and the development of novel nanozymebased drugs for inhibition of ferroptosis to protect organs in SAP remains to be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 As a lipid repair enzyme, GPX4 is a key factor of ferroptosis, and the dysfunction or abnormal level of FTH1 will cause an increase in intracellular iron amount, allowing us to promote the occurrence of ferroptosis. 16,18 However, research of SAP treatment is still at a preliminary stage of exploration, and the development of novel nanozymebased drugs for inhibition of ferroptosis to protect organs in SAP remains to be challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation